การพัฒนาหนังสืออิเล็กทรอนิกส์หลักและวิธีสอนกระบี่กระบอง - เสาว์เฉลิม, อัจฉรา; บัตรเจริญ, จุฑามาศ (Journal of Education Studies, Chulalongkorn University, 2019)
This research was quasi-experimental research. The purposes were to develop an electronic book (e-book) on the principles and methods of teaching Krabi-Krabong (Thai Fencing) and to study students’ satisfaction towards this e-book. The population sample for this study were sophomores at a university in Bangkok. These students were enrolled in a Krabi-Krabong class in the second semester of the academic year 2015. Simple random sampling was used to select 30 qualified students. The research tools comprised: 1) an e-book, 2) a quality evaluation form, 3) an achievement test, and 4) a questionnaire. Content validity was judged by 6 experts. The index of correspondence between question and purpose was greater than 0.5. The collected data was analyzed using standard deviation, mean and independent samples t-test. The research results found: 1) the effectiveness of an electronic book on the principles and methods of teaching Krabi-Krabong was at 86.17% which met the 80/80 standard efficiency criterion. This showed very good quality of = 4.78 2). After the learning scores came out to much higher than the pretest scores at .05 of the statistically significant level. 3) The satisfaction, of using an e-book to learn, displayed at a very high level of = 4.75 Therefore, an electronic book on the principles and methods of teaching Krabi-Krabong could be used as a teaching material.